Analisis Varian Tekanan Mesin Hydraulik Dan Persentase Filler Pada Kampas Rem AMC Berpenguat BFA Dan SIO₂ Terhadap Nilai Koefisien Gesek ASTM G99-05 - Alfan, Sudrian; Pranandita, Nanda; Sukanto, Sukanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The safety aspect is important that must be considered in vehicles, because components that not comply with standards can pose serious risks. The use of asbestos also have a negative impact on health, caused by exposure to contaminated air and can damage respiratory system. This research aims to develop environmentally friendly brake linings, as well as studying the effect of two-way hot compaction pressure and reinforcement volume percentage on friction coefficient. This research uses powder metallurgy method which starts from the process mixing recycled aluminium powder, silica sand, and palm oil boiler fly ash, using ball mill machine (BPR 10:1) at speed 90 rpm, for 6 hours. Compaction was carried out in two directions with pressure variants of 5000, 5400 and 5800 Psi at temperature 350°C for 10 minutes. The sintering process was carried at temperature 600°C with holding time of 10 minutes. Friction coefficient testing is carried out to calculate the wear by following the ASTM G99-05 standard. The results show that increasing the percentage reinforcement and compaction pressure can increase friction resistance, highest wear value of 0.055 gr with parameters (84% reinforcement, pressure 5000 Psi) and the lowest wear value of 0.032 parameters (92% reinforcement, pressure 5800 Psi).